Diallel analysis of tropical and temperate sweet and supersweet corn inbred lines - Suzukawa, Andréia; Pereira, Carolina; Garcia, Mayara; Contreras-Soto, Rodrigo; Zeffa, Douglas; Coan, Marlon Mathias; Scapim, Carlos (Revista Ciência Agronômica, 2018)
The number of sweet corn cultivars adapted to the climatic conditions and with agronomic traits recommended to the Brazilian market is still limited. Thus, the aim was to investigate the general and specific combining ability (GCA and SCA, respectively) in relation to the grain yield (GY) and total soluble solid (TSS) contents of seven lines of sweet corn (su1) and eight lines of supersweet corn (sh2) by diallel crosses. For TSS, the inbred lines SC6 and SC7 of sweet corn, and SSC7 and SSC8 of supersweet corn showed higher GCA effect. For GY, the inbred lines SC1 and SC2 of sweet corn and SSC4 and SSC6 of supersweet corn showed higher GCA effect. For TSS in sweet corn, the hybrids ‘4 × 6’ and ‘1 × 7’ showed the superior Ŝij estimates across all evaluated environments. For GY, the hybrid ‘5 × 7’ was the most relevant because it showed higher Ŝij  estimates in most of the evaluated environments. Additionally, the hybrids ‘1 × 4’, ‘3 × 4’, and ‘1 × 7’ showed positive Ŝij values across all environments. In supersweet corn, the hybrids ‘2 × 8’, ‘3 × 6’, and ‘5 × 6’ should be selected as the most promising for both traits (TSS and GY), because they presented positive and high Ŝij estimates across the six environments.